A4.14 Role of Different Adiponectin Receptors in Adiponectin Signaling In Rheumatoid Arthritis Synovial Fibroblasts. (25th February 2013) - Khawaja, K; Frommer, KW; Schäffler, A; Büchler, C; Rehart, S; Lehr, A; Müller-Ladner, U; Neumann, E
Abstract : Objectives: Adiponectin levels were found to be increased in the synovial fluid of rheumatoid arthritis (RA) patients suggesting a role in the pathophysiology of the disease. RA synovial fibroblasts (SF) are known to be a key cell in RA and to express adiponectin in vivo. Adiponectin exists in four isoforms, namely the globular, low molecular weight (LMW or trimer), middle molecular weight (MMW) and high molecular weight (HMW) form. These isoforms act by binding to its receptors AdipoR1, AdipoR2, PAQR3 and PAQR10, which are expressed by various cells. Subsequently, different intracellular signalling pathways are activated including AMPK, p38MAPK, and FAK. The purpose of the present study was to determine the adiponectin receptor expression and the specificity of the adiponectin receptors to the respective adiponectin isoforms mediating different signalling pathways in RASF. Methods: AdipoR1, AdipoR2, PAQR3 and PAQR10 mRNA and protein expression were analysed in RASF by Real-time PCR, Western blotting, and immunocytochemistry. AdipoR1 and AdipoR2 down-regulation by siRNA via nucleofection technology and lentiviral transduction were performed followed by signalling analysis via Western blots. Results: Real-time PCR and Western blotting results showed that cultured RASF express AdipoR1, AdipoR2, and PAQR3 but not PAQR10. This was further confirmed by immunocytochemical analysis. Transfection of siRNA specific for AdipoR1, AdipoR2 and PAQR3 via nucleofection showed successful receptor down-regulation at mRNA level but no effect was observed at protein level even after 10 days, most likely due to the long receptor half-life on the cell surface. However, lentiviral transduction showed successful down-regulation of AdipoR2 at mRNA as well as at protein level after 5 weeks (approx. 5 fold). AdipoR2 knockdown in RASF showed a reduction in adiponectin-induced p38MAPK signalling. Conclusions: Our results show that RASF isolated from synovium of RA patients express the adiponectin receptors AdipoR1, AdipoR2 and PAQR3. Down-regulation of these adiponectin receptors by lentiviral transduction was found to be a more efficient technique as compared to siRNA transfection, which will facilitate to study their role in signalling. Moreover, the induction of the p38MAPK pathway by adiponectin seems to be dependent on AdipoR2. Funding: This work was supported by the German research society (NE1174/8–1).